Correlation between 25-hydroxyvitamin D level and arterial elasticity in middle-aged and elderly cadres in Guiyang, China: A retrospective observational study. Issue 18 (7th May 2021) - Shi, Lan; Zhang, Qiao; Song, Sai-Nan; Ma, Lin; Chang, Qing; Zhang, Shuang-Yun
Abstract : Abstract: There is evidence that serum 25-hydroxyvitamin D [25-(OH) D] levels may be associated with cardiovascular disease and its risk factors. This study aimed to investigate the relationship between 25-(OH) D levels and blood pressure (BP), blood lipids, and arterial elasticity in middle-aged and elderly cadres in China. In this retrospective study, we included 401 civil servants and cadres aged >42 years who underwent medical examinations at Guiyang Municipal First People's Hospital, China in 2018. The participants were assigned to deficiency (⩽20 ng/mL), insufficiency (20–30 ng/mL), and sufficiency (≥30 ng/mL) groups according to 25-(OH) D levels in their blood. Demographics, brachial–ankle pulse wave velocity (baPWV), BP, ankle–brachial index (ABI), and blood lipids were compared among groups. The associations between 25-(OH) D and other parameters were evaluated using linear regression analysis. Median (range) 25-(OH) D levels in the deficiency (n = 162), insufficiency (n = 162), and sufficiency (n = 77) groups were 15.32 (2.93–19.88), 25.12 (20.07–29.91), and 33.91 (30.23–82.42) ng/mL, respectively. There were significant differences in systolic BP, pulse pressure, baPWV (left and right sides), ABI (left side), high-density lipoprotein-cholesterol, and triglycerides (TGs; all P < .05) among groups. Multivariate linear regression revealed that TG, left baPWV, and right baPWV were significantly negatively correlated with 25-(OH) D levels (all P < .05). In this study, 25-(OH) D levels were found to be associated with TG, left baPWV, and right baPWV values. 25-(OH) D deficiency may be associated with reduced arterial elasticity.